Does the Use of Volumetric Modulated Arc Therapy Reduce Gastrointestinal Symptoms after Pelvic Radiotherapy?. Issue 1 (January 2018) - White, K.L.; Varrassi, E.; Routledge, J.A.; Barraclough, L.H.; Livsey, J.E.; McLaughlin, J.; Davidson, S.E.
Abstract: Aims: Growing numbers of patients with cancer are surviving after treatment with pelvic radiotherapy. We evaluated the technique of volumetric modulated arc therapy (VMAT), which delivers a decreased dose to the organs at risk. We aimed to determine outcomes of this technique in terms of patient-reported acute toxicity and late effects and correlate the frequency of gastrointestinal symptoms with the volume of bowel receiving radiation dose. Materials and methods: Patients who were to receive VMAT for gynaecological malignancy completed patient-reported outcomes at baseline, the end of treatment, 8 weeks and 1 year. The rates of patient-reported toxicity were correlated with the volume of bowel irradiated. Results: The frequencies of patient-reported gastrointestinal symptoms increased in the acute toxicity phase and tended to improve at 1 year, with the exception of faecal incontinence and rectal bleeding ( P  < 0.05). There was not a strong association between the volume of small bowel that was irradiated ( P  > 0.05 at all dose levels) and reported toxicity, suggesting that other factors are involved in the development of toxicity. Conclusion: Although VMAT decreases the dose delivered to the small bowel, this does not translate into a reduction in patient-reported toxicity. Highlights: Patients treated with volumetric modulated arc therapy report significant acute bowel symptoms Faecal incontinence and rectal bleeding remain an issue at 1 year No association between small bowel volumes and patient reported bowel symptoms